Epidemiological characteristics of injuries among elite adolescent flat-water kayak and canoe athletes - Gao, Ke; Deng, Yixin; Zhou, Xiao; Zeng, Hongtao; Kimura, Tomohiro; Shen, Shaoshuai; Pan, Ziheng; Han, Na (Frontiers in Public Health, 2025)
BackgroundSport injuries are now becoming a major issue affecting training in paddle sports. This study was to investigate the distribution and prevalence of injuries among adolescent flat-water kayak and canoe athletes.MethodsWe performed a retrospective design study to survey one-hundred forty Chinese elite adolescent flat-water kayak and canoe athletes (89 kayakers and 51 canoers; 81 males and 59 females, with an average age of 16 years) using a self-reported questionnaire. The questionnaire investigated basic information and kayak- and canoe-related injuries over the past year. The primary outcome measures were the distribution of kayak- and canoe-related injuries and the injury rate per 1,000 training hours with a 95% confidence interval (CI).ResultsA total of 207 injuries were reported from all the participants, including 138 injuries related to flat-water kayak and 69 injuries related to canoe. The most common injured site in flat-water kayak athletes was the lower back, followed by the shoulder, wrist, and knee. In flat-water canoe athletes, the most common injured site was the shoulder, followed by the lower back, back, and knee. Regarding injury rates, the flat-water kayak athletes showed 0.90 injuries per 1,000 training hours (95% CI = 0.75–1.05). The female kayak athletes had 1.02 injuries per 1,000 training hours (95% CI = 0.81–1.23), while the male kayak athletes had 0.74 injuries per 1,000 training hours (0.53–0.95). Notably, the injury rate per 1,000 training hours was significantly higher in female canoe athletes (1.51, 95% CI = 1.05 to 1.98) than in male canoe athletes (0.47, 95% CI = 0.30 to 0.64).ConclusionThe findings indicated that flat-water kayak- and canoe-related injuries mostly involved in the shoulder and lower back among Chinese elite adolescent athletes, with female athletes, particularly in canoe, being more susceptible to injury. These insights are critical for enhancing athlete injury prevention strategies and providing coaches and athletes with comprehensive reference data on injury.